The West Balkans between the EU, the USA, and Russia: Challenges and options - Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2009)
The European Union's success in its self-defined role as the driving force of conflict resolution in the West Balkans depends to a large extent on its accurate understanding of the interests and actions of the other two most important external actors: the USA and Russia. Russia has more often been the West's adversary than ally in the Western Balkans in the course of the last two decades since the disintegration of Yugoslavia started. In particular, the Kosovo crises and NATO's war against Serbia in the year 1999 caused deep rifts in Russia's relationship with the West. Russian President Dmitri Medvedev will visit Serbia at the end of this October signalling Moscow's continuing interest in the region. Russia is striving to limit US influence in the Western Balkans and to increase its own leverage. Russia's two main means to achieve this goal is to continue supporting Serbia's struggle to preserve its legal claim over Kosovo and to build the large gas pipeline 'South Stream' which will further increase Russia's importance for Europe's energy security
Keywords: 320